2010
DOI: 10.1007/s00438-010-0586-8
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin A suppresses expression of the human melanoma-associated gene ABCB8

Abstract: The role of the ABCB8 gene in human cells is poorly understood, although it has been suggested to be involved in multidrug resistance in some types of cancers (e.g., melanomas). In this study, the main mechanism of transcriptional regulation of the ABCB8 gene was characterized. EMSA and ChIP assays revealed that the transcription factor Sp1 binds to the ABCB8 core promoter region, and Sp1 consensus elements were crucial for promoter activity in a luciferase reporter gene assay. Mithramycin A, an inhibitor of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…AAEL006717) of human ABCB7 in the dengue vector, Aedes aegypti , was reported to be upregulated in an insecticide resistant strain [9,63]. The function of human ABCB8 is not well understood, but it was shown to mediate resistance against the chemotherapeutic agent doxorubicin in melanoma cells [64,65]. Also, Ichikawa et al found that disruption of the mouse orthologue of human ABCB8 lead to cardiomyopathy and decreased mitochondrial iron export [66].…”
Section: Resultsmentioning
confidence: 99%
“…AAEL006717) of human ABCB7 in the dengue vector, Aedes aegypti , was reported to be upregulated in an insecticide resistant strain [9,63]. The function of human ABCB8 is not well understood, but it was shown to mediate resistance against the chemotherapeutic agent doxorubicin in melanoma cells [64,65]. Also, Ichikawa et al found that disruption of the mouse orthologue of human ABCB8 lead to cardiomyopathy and decreased mitochondrial iron export [66].…”
Section: Resultsmentioning
confidence: 99%
“…Mith suppresses the expression of the human melanomaassociated gene ABCB8 and has potential therapeutic applications for treating melanoma patients (Sachrajda and Ratajewski, 2011). Mith also decreased VEGF and XIAP to induce apoptosis and inhibit tumor cell migration in glioma cells (Seznec et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We screened a chemical library of 1120 compounds using cells that were transfected with the previously described ABCB8 promoter construct [30]. The screening resulted in the identification of approximately 20 compounds that activated or repressed the transcriptional properties of the ABCB8 promoter (data not shown).…”
Section: Ac-93253 Influences the Expression Of The Abc Melanoma Gene mentioning
confidence: 99%